1999
DOI: 10.1046/j.1365-3024.1999.00234.x
|View full text |Cite
|
Sign up to set email alerts
|

Malaria parasite‐specific Th1‐like T cells simultaneously reduce parasitemia and promote disease

Abstract: CD4+ T cells have been implicated in immunity to the blood stages of malaria and cytokines associated with both monocyte and T cell activation have been implicated in disease. To determine whether specific T cells capable of inhibiting parasite growth can also mediate pathology we have transfused populations of Plasmodium berghei-specific T cells into normal and immunodeficient naive mice. We observed that they could inhibit parasite growth but were unable to save the animals which exhibited significantly grea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
60
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(60 citation statements)
references
References 58 publications
0
60
0
Order By: Relevance
“…Consistent with the enhanced acute-phase response, mice with a polarized Th1 response show marked weight loss relative to infected wild-type mice upon infection with a variety of pathogens, including S. mansoni and Plasmodium berghei (25)(26)(27). In addition to cachexia, mice infected with P. berghei in a Th1 environment suffered extensive coagulative necrosis of the liver despite lower parasitemia, and IL-10/4 KO mice infected with S. mansoni had significantly more hepatotoxicity, reflected by elevated aminotransferase levels (26,27).…”
Section: Discussionmentioning
confidence: 74%
“…Consistent with the enhanced acute-phase response, mice with a polarized Th1 response show marked weight loss relative to infected wild-type mice upon infection with a variety of pathogens, including S. mansoni and Plasmodium berghei (25)(26)(27). In addition to cachexia, mice infected with P. berghei in a Th1 environment suffered extensive coagulative necrosis of the liver despite lower parasitemia, and IL-10/4 KO mice infected with S. mansoni had significantly more hepatotoxicity, reflected by elevated aminotransferase levels (26,27).…”
Section: Discussionmentioning
confidence: 74%
“…The role of CD4 ϩ T cells during the blood stage of infection is not completely clear, but many examples demonstrate the importance of CD4 ϩ T cells in the control of blood-stage malaria (1). However, it was shown that P. berghei-specific CD4 ϩ T cells have the ability to promote disease (5,11,37). Symptoms were attenuated by immunosuppressive drugs (38,39) or by removing the thymus (40).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a direct interaction of T cells and parasites or infected cells is unlikely. However, the contribution of CD4 ϩ T cells in acquired immunity to blood-stage malaria was demonstrated using several strains of Plasmodium parasites in mice (1)(2)(3)(4)(5). These studies suggested that malaria-specific T cells, especially cytokine-secreting Th1 cells, regulate other antiparasitic effector systems.…”
mentioning
confidence: 99%
“…This approach was followed because we (19,20) and others (21) have shown that T cells can adoptively transfer protection to malaria and because it is possible that the vaccination protocol (above) was unable to induce sufficient numbers of T cells. Furthermore, the phenotypes of vaccine-induced T cells is likely to be heterogeneous.…”
Section: Protection Against P Yoelii Ym Infection By Adoptively Tranmentioning
confidence: 99%